The Factors Influencing Husband’s Support for Exclusive Breastfeeding at Suoh Medical Center Clinic - Anggriani, Yunita; Supinah , Pipin (Indonesian Journal of Health Research and Development, 2023)
Breastfeeding is crucial for newborns, particularly throughout their early years of life. Accordingly, throughout the first six months of life, newborns should only be breastfed and not given any other foods or beverages. Government Regulation of the Republic of Indonesia Number: 33 of 2012 details the national policy that the government has also implemented on the exclusive breastfeeding program. According to Article 6, a mother who gives birth is required to nurse her child exclusively. Mothers' success in delivering exclusive breastfeeding cannot be separated from family support, especially husbands who always give encouragement and care. The purpose of this study was to identify the variables that will affect husband support for exclusive breastfeeding in 2023 at the Suoh Medical Center Clinic. Analytical survey research using a cross-sectional methodology was the methodology employed. This study included husbands with infants between the ages of six and twelve months. The number of respondents in this study's sample was thirty. Saturated sampling, or chi-square bivariate analysis, was the sample method employed. The chi-square test results revealed that knowledge had a ρ value of 0.000 <0.05, socio-culture had a ρ value of 0.002 <0.05, and education level had a significant value of 0.001 <0.05. The conclusion was that there was a correlation between education, knowledge, and socio-culture with exclusive breastfeeding. Suggestions for health workers in providing knowledge about exclusive breastfeeding need to involve husbands, who are the primary motivators of mothers in breastfeeding babies.